3D printing and crimes with use of firearms - Ziobroń, Agata (Studia Iuridica Toruniensia, 2021)
In the last decade 3D printers became cheaper and more accessible. In the literature, potential threats of that techniques are pointed – possibility of its use in the purpose to commit illicit acts what may appear in reaction of legal regulations of states in the Europe and world. In the article it was taken an attempt to analyse documented cases of use 3D printers in the context of statutory marks typified in the articles 263 and 255a of Polish Criminal Code and to answer the question whether current provisions of Criminal Code referring to the firearms are enough comprehensive to live up to new technologies and problems connected with their possessing and use which states of West Europe, Australia and the USA cope with.